South Africa's common society - Simons, Jack (My University, 1991)
I circulated a draft paper in February 1989 with the title "South Africa's Civil War: Revolution and Counter-Revolution". It had two parts, one called "Resistance and Repression", the other "South Africa's Common Society". Together they made out a case for identifying the struggle as a civil war arising out of a revolutionary situation. The terms are complementary, not contradictory. A civil war by definition is an armed conflict between combatants who are citizens of the same state, belong to the same society, and take up arms in a struggle for political power. The most bitter and ruinous war of the last century was the civil war fought in the United States in 1861/2 between the slave-owning Confederacy and the Union of free labour states. (2) A South African example of an imperial war was Britain's war of 1899-1902 against the Boer republics, fought by an aggressive power to establish control over the whole of Southern Africa in keeping with the ambition of Cecil John Rhodes (1852-1902) to paint the map red from Cape to Cairo.
African Studies Seminar series. Paper presented February 1991
Keywords: South Africa. Politics and government